Ventricular rate monitoring as a tool to predict and prevent atrial fibrillation-related inappropriate shocks in heart failure patients treated with cardiac resynchronisation therapy defibrillators. Issue 11 (28th March 2014) - Ricci, Renato Pietro; Pignalberi, Carlo; Landolina, Maurizio; Santini, Massimo; Lunati, Maurizio; Boriani, Giuseppe; Proclemer, Alessandro; Facchin, Domenico; Catanzariti, Domenico; Morani, Giovanni; Gulizia, Michele; Mangoni, Lorenza; et al.
Abstract : Objective: Inappropriate implantable cardioverter defibrillators (ICD) therapies have been associated with multiple adverse effects, including worse quality of life and prognosis. We evaluated the possibility of predicting atrial fibrillation (AF)-related inappropriate ICD shocks through continuous monitoring of device diagnostics. Methods: 1404 ICD patients were prospectively followed in an observational research by 74 Italian cardiology centres. Device diagnostics stored daily information on AF duration and ventricular rate (VR) during AF. Uncontrolled VR was defined as mean VR>80 beats per minute (bpm) and maximum VR>110 bpm. Expert electrophysiologists reviewed the ventricular tachycardia/ventricular fibrillation (VT/VF) episodes electrograms, stored in the device memory, and classified appropriate detections, inappropriate detection mechanisms and ICD therapy outcomes. Results: Over a median follow-up of 31 months, 511 (36%) patients suffered spontaneous VT/VF, which were treated by ICD shocks in a subgroup of 189 (13%) patients. Inappropriate detections occurred in 232 (16%) patients, and inappropriate ICD shocks in 101 (7%) patients. AF was the cause of inappropriate shocks in 60 patients. AF caused 144 inappropriate shocks: 53% of all inappropriate shocks. The likelihood of experiencing AF-related inappropriate shocks was 2.4% at 1 year and 6% at 5 years. Uncontrolled VR during AF proved to be an independent predictor of AF-related inappropriate shocks (OR=3.02, p=0.006); an alarm set at a VR>90 bpm or 100 bpm was associated with prediction of AF-related inappropriate shocks with a sensitivity of 73% or 62%, respectively. Conclusions: AF is the most common cause of inappropriate shocks in ICD patients. Continuous remote monitoring of VR during AF would promptly and efficiently predict AF-related inappropriate shocks. Clinical trial registration: http://clinicaltrials.gov/ct2/show/NCT01007474